Síntese de derivados do estigmasterol e do ácido ursólico e avaliação de suas atividades biológicas - Borges, Nalin de Seixas (2014)
The present work describes the synthesis of twenty-two new derivatives (4-25) from stigmasterol (1) and seven new derivatives (26-32) from ursolic acid (2) via esterification and coupling reactions with different amino acids. All the structures of the compounds were confirmed by 1H and 13C NMR. The derivatives were tested for their antimicrobial activity, antitumor activity against cancer cells HT -29 (colorectal) and inhibition of POP, AChE and BChE enzymes. In antimicrobial activity among the compounds tested, ursolic acid (1) showed the greatest potential for inhibition. The results obtained from enzyme inhibition tests were satisfactory, generally the activities of the starting compounds 1 and 2 were increased after the introduction of the amino acids. Among the derivatives evaluated, ursolic-proline-proline-OH acid (32) showed the highest inhibitory capacity of AChE and BChE enzymes and may be considered a dual cholinesterase inhibitor, which can provide greater efficacy in the treatment of Alzheimer's disease. In the evaluation of the antitumor effect, after the first 24 h, most of ursolic acid derivatives showed inhibition effect in cell viability between 33.7 and 70%. After 72 h, the derivative 32 showed the best performance because it did not increase the number of viable cells at any concentration tested, indicating that this compound may be a candidate for antitumor drug.